An Introduction to the Police Procedural: A Subgenre of Detective Genre - Fitria Akhmerti Primasita; Heddy Shri Ahimsa-Putra (Humaniora, 2019)
Based on a library research, this paper aims at introducing the police procedural as a subgenre of detective genre. To achieve the aim, this paper elaborately discusses three definitions of the police procedural. The discussion shows that experts have apparently provided a working definition of the police procedural after having identified how the new variant is different from, and yet the same as the “parent” genre. While the third definition discussed puts emphasis on the authentic and realistic aspects of the police procedural, the first two definitions can be used as a reference to elaborately discuss the police procedural as a variant or subgenre of the detective genre. The police procedural retains the basic conventional elements of the detective genre—plot and motifs, character, setting, theme, and props, but it twists these elements and turn them into inventions to keep the interest of the readers and viewers. Having established itself as a subgenre, the police procedural grows to become formulaic by creating its own conventions. It is a formula that is generally employed by writers and has come to be expected by readers or viewers. By doing so, the police procedural has helped the detective genre as its “parents” genre stay popular.